Comparison of Neutralizing Antibody Response Kinetics in Patients with Hand, Foot, and Mouth Disease Caused by Coxsackievirus A16 or Enterovirus A71: A Longitudinal Cohort Study of Chinese Children, 2017-2019 - Zhou, Yonghong (AMER ASSOC IMMUNOLOGISTS, 2022)
10.4049/jimmunol.2200143